Implementation of Sharia Dress Awareness Based on the Code of Ethics Among Islamic Education Study Program Students of the 2021 Class of the Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry Banda Aceh - Syafruddin (MADINA : Journal of Islamic Studies, 2025)
UIN Ar-Raniry Banda Aceh implements a dress code of ethics for students of the Faculty of Tarbiyah and Teacher Training which emphasizes dress standards in accordance with the values of modesty and Islamic teachings. This provision requires students to wear neat, polite, and sharia-compliant clothing, such as wearing a hijab that covers the chest and wearing clothing that is not tight, transparent, or has slits. This study aims to: 1) Analyze the level of awareness of female PAI Study Program students of the 2021 intake regarding the implementation of the sharia dress code of ethics on campus, 2) Identify the implementation of sharia clothing in the daily lives of female students in accordance with the applicable code of ethics, and 3) examine the factors that influence their compliance with sharia dress rules. The research method used is a qualitative approach with data collection techniques in the form of structured interviews, participant observation, and documentation. The results of the study showed that female students' awareness of the dress code of ethics was divided into two groups. First, female students who have dressed according to the code of ethics standards by wearing loose, non-transparent clothing, and in accordance with the principles of Islamic law; second, female students who have not fully complied with the code of ethics by still wearing tight, transparent clothing that does not meet the code of ethics standards. In general, the implementation of sharia clothing is quite good, although there are still some that are not optimal. Factors that influence awareness of sharia clothing consist of internal factors, such as religious understanding, self-awareness, and personal motivation, as well as external factors, including social environment, educational background, campus policies, and the influence of social media.